Effect of glycosphingolipids on osteoclastogenesis and osteolytic bone diseases - Ersek, Adel; Karadimitris, Anastasios; Horwood, Nicole (Frontiers in Endocrinology, 2012)
Alterations in glycosphingolipid production results in lysosomal storage disorders associated with neurodegenerative changes. In Gauchers disease, the patients also develop osteoporosis that is ameliorated upon treatment for the underlying defect in glycosphingolipid metabolism. The role of glycosphingolipids in osteoclast and osteoblast formation is discussed here as well as the potential therapeutic uses of already approved drugs that limit glycosphingolipid production in bone loss disorders such as multiple myeloma and periodontal disease.